Subtype-Specific Prevalence of Hepatitis C Virus NS5A Resistance Associated Substitutions in Mainland China - Lu, Jie; Feng, Yupeng; Chen, Lichang; Zeng, Zhengyu; Liu, Xianliang; Cai, Wei; Wang, Hui; Guo, Xiaolei; Zhou, Huijuan; Tao, Wanyin; Xie, Qing (Frontiers in Microbiology, 2019)
Resistance associated substitutions (RASs) can reduce the efficacy of direct-acting antiviral agents (DAAs) targeting hepatitis C virus (HCV) and lead to treatment failure. Clinical data of HCV NS5A RASs prevalence are limited in China and need to be investigated. A total of 878 unique patient samples with different genotypes (GT) (1b: n=489, 2a: n=203, 3a: n=60, 3b: n=78, 6a: n=48) were collected from around mainland China by KingMed Laboratory and analyzed for NS5A RASs distribution by Sanger sequencing. Phylogeographic analyses based on NS5A domain 1 sequences indicated circulation of both locally and nationally epidemic strains. Relatively high frequency of Y93H (14.1%) was only detected in GT1b but not in other subtypes. High frequency of L31M was found in both GT2a (95.6%) and GT3b (98.7%) sequences. Due to the overlapping incidence of A30K, 96% of GT3b isolates had NS5A RASs combination A30K + L31M, which confers high levels of resistance to most NS5A inhibitors. No RASs were detected in GT6a strains. Meanwhile, baseline NS5A RASs fingerprints were also evaluated in 185 DAA treatment-naive GT1b patients with next generation sequencing method. Patients presenting with Y93H had a statistically higher entropy of HCV NS5A sequences. Taken together, subtype-specific distribution patterns of NS5A RASs were observed. GT1b patients with higher HCV complexity tend to have a greater chance of Y93H presence, while GT3b patients are naturally resistant to current NS5A inhibitors and their treatment may pose a challenge to real-world DAA application.